Efficacy, safety and tolerability of autologous platelet rich plasma injection in the treatment of lateral epicondylitis - Bhan, Kavyansh; Kenjle, Randhir (International Journal of Research in Orthopaedics, 2019)
Background: To evaluate the effects of platelet-rich plasma (PRP) infiltration in patients with lateral epicondylitis of the elbow. Methods: A randomized, prospective study on 60 patients with lateral epicondylitis of the elbow was conducted at Ruby Hall Clinic, Pune. The patients were randomized and evaluated after receiving infiltration of three milliliters of PRP, or methyl prednisolone. The base-line evaluation was done using visual analog score (VAS) and modified Mayo performance index for elbow (MAYO). Re-evaluation was after 1 and 6 months of the procedure. Statistical analysis was done using independent t-test. Results: After 6 months of treatment with PRP, patients with lateral epicondylitis had a statistically significant improvement in their VAS (p<0.05) in contrast to steroid. However, no statistical difference in modified Mayo performance index was found between the two groups at 1 and 6 months after intervention. Conclusions: Treatment of patients with lateral epicondylitis with PRP reduces pain and is better tolerated than steroid therapy. Thus, the novel PRP therapy can be considered as a primary approach to treat patients of lateral epicondylitis conservatively.